Effects of wind loads and floating bridge motion on intercity bus lateral stability. Issue 212 (May 2021) - Sekulic, Dragan; Vdovin, Alexey; Jacobson, Bengt; Sebben, Simone; Johannesen, Stian Moe
Abstract: Efficient transportation is an important factor for regional socio-economic growth. Excitations from wind loads and road motions can influence vehicle-driver behaviour in a way that may impair transportation. This is especially true in open areas such as long-span bridges. This paper investigates the influence of wind loads and floating bridge motions on bus lateral stability for the straight concept solution across Bjørnafjorden in Norway. For this investigation, an 8-degree-of-freedom model of a two-axle coach is used. The defined driver model is based on the pure pursuit path tracking method. The vehicle deviation from the path is found to increase with increasing bus speed. This deviation is significant after the vehicle enters the bridge (e.g., over 0.5 ​m for a speed of 90 ​km/h). At 108 ​km/h, the windward rear wheel loses contact, indicating the potential risk of vehicle roll-over. The mean and root-mean-square values of the handwheel steering angle increase with increasing speed, which might cause difficulty for the driver to control the vehicle. Simulation results suggest that the bus can suitably enter the bridge at a lower speed (e.g., 72 ​km/h) with the possibility of increasing the speed (up to 90 ​km/h) after approximately 2 ​km of travelled distance. Highlights: Floating bridge vertical displacements with low angular spatial frequencies prevailing. Path deviation increases with increasing bus speed. Handwheel steering angle signals oscillate around a mean value. The mean value increases with increasing speed. Winward rear wheel could lose contact with the floating bridge deck at the highest speed.